Educational Benefits and Cognitive Health Life Expectancies: Racial/Ethnic, Nativity, and Gender Disparities. (24th August 2020) - Garcia, Marc A; Downer, Brian; Chiu, Chi-Tsun; Saenz, Joseph L; Ortiz, Kasim; Wong, Rebeca
Abstract: Background and Objectives: To examine racial/ethnic, nativity, and gender differences in the benefits of educational attainment on cognitive health life expectancies among older adults in the United States. Research Design and Methods: We used data from the Health and Retirement Study (1998–2014) to estimate Sullivan-based life tables of cognitively healthy, cognitively impaired/no dementia, and dementia life expectancies by gender for older White, Black, U.S.-born Hispanic, and foreign-born Hispanic adults with less than high school, high school, and some college or more. Results: White respondents lived a greater percentage of their remaining lives cognitively healthy than their minority Black or Hispanic counterparts, regardless of level of education. Among respondents with some college or more, versus less than high school, Black and U.S.-born Hispanic women exhibited the greatest increase (both 37 percentage points higher) in the proportion of total life expectancy spent cognitively healthy; whereas White women had the smallest increase (17 percentage points higher). For men, the difference between respondents with some college or more, versus less than high school, was greatest for Black men (35 percentage points higher) and was lowest for U.S.-born Hispanic men (21 percentage points higher). Discussion and Implications: Our results provide evidence that the benefits of education on cognitive health life expectancies are largest for Black men and women and U.S.-born Hispanic women. The combination of extended longevity and rising prevalence of Alzheimer's disease points to the need for understanding why certain individuals spend an extended period of their lives with poor cognitive health.